Analisis Penerimaan Pengguna E-Learning Fakultas Ilmu Komputer Menggunakan Model Unified Theory of Acceptance And Use of Technology (UTAUT) dan Task Technology Fit (TTF) - Qori' Ima Ma'rifatin; Yusi Tyroni Mursityo; Mochamad Chandra Saputra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Faculty of Computer Science (Filkom) has applied moodle based e-learning with the name E-learning Faculty of Computer Science-UB. This research has a purpose to determine what factors that affecting the acceptance of e-learning in computer science faculty students. The model used is the integration of Unified Theory of Acceptance and Use of Technology (UTAUT) and Task Technology Task (TTF) using parametric and nonparametric methods. Collecting data using the questionnare online and offline with the minimum numberof respondent that will be used for this research is 98. The collected data is tested the basic assumption test of normality, linearity and homogenty. The data that passed the basic assumption test wast done by parametric using the simple linear regression, while those did not pass the basic assumption be analyze using non parametric using Kendall Tau method. The results of the study show that the influence of performance expectancy on user adoption is in the low category of 12.7%, social influence on user adoption is in the perfect category of 68.1%, task technology fit to the user adoption is categorized as weak by 10.4%, technology characteristic to task technology fit in the medium category at 59.0%, however, all of these variables have several indicators that still need improvement.